A numerical model study of steady flow through bell-shaped stenoses with and without asymmetry. (21st September 2010) - Mandal, D.K.; Manna, N.K.; Chakrabarti, S.
In the present paper, the effect of symmetrical and asymmetrical bell shaped stenoses on wall pressure drop, streamline contour, and rise in wall shear stress (WSS) for the progression of the disease, atherosclerosis has been investigated numerically. The governing equations have been solved by finite volume method. It is revealed from the study that the impact of wall pressure and peak WSS on progression of disease are always high for asymmetrical shaped stenosis. The impact of asymmetrical shape on plaque deposition zone is less, if the aggravation changes the shape of stenosis due to change in stricture length only keeping percentage of restriction same. Whereas, the impact of asymmetrical shape on plaque deposition zone will be high, if shape of stenosis changes by increasing both stricture length and percentage of restriction.